ANALISIS DAMPAK PELAKSANAAN OTONOMI KHUSUS TERHADAP PENINGKATAN KESEJAHTERAAN MASYARAKAT ASLI PAPUA DI KABUPATEN MIMIKA - Supriyatin .; Tharsisius Pabendon (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2017)
This research aims to measure the implementation of Papua special autonomy towards the improvement of the welfare of Papua indigenous people in Mimika Regency. There are four indicators for this research, which are sense of security, prosperity, freedom, and identity. The data collected through observation, questionnaire, and literature review. Data analysis used frequency distribution analysis by giving scale to question asked. The result shows that the average of the implementation of Papua special autonomy towards the improvement of the welfare of Papua indigenous people in Mimika Regency is 54,37%. It means the improvement of the welfare of Papua indigenous people in Mimika Regency is good enough.